The Principle of Balance E-Contracts in Paylater features in E-Commerce - Giza'a Jati Pamoro (Notaire, 2022)
AbstractThe development of digital technology makes a lot of changes against people behavior, one of which are buying and selling activities in e-commerce. This study aims to analyze a implementation the princinple of balance in e-contracts specificities a paylater payment feature contained in e-commerce. The existing of e-commerce makes a people shift from a conventional contracts (physical) to electronic contracts (e-contracts). Behind the conveniences and sophistication from e-contracts, there is a weakness and significant impact such as imbalance from that clauses and then makes the users (society) not more paying attention against that clauses, even that contracts. This study uses doctrinal legal research method with statutory and conceptual approach. Based on the analyze, between a company (e-commerce) and users (societies) there is imbalance in a contracts, because a company always feels superior than users, so that users only follow anything provisions which made by a company without notice a principle of balance in a contracts. the company should be able to provide several options in the clause, so that users can really understand the legal actions carried out by the parties.Keywords: Principle of Balance; E-Contracts; E-Commerce; Paylater.